SOSOK MUDA KI PANDU NUR PRASTIYO - Salim (Akademi Seni dan Desain Indonesia Surakarta, 2024)
Shadow puppets are one of the identities of Javanese people in the life of Javanese society itself. Until now, shadow puppets remain an important characteristic of Javanese culture. In this case, shadow puppets are often also called wayang purwa. In the shadow puppet (purwa) performance, the puppeteer plays a very important role in the performance. The puppeteer is required to have expertise and skills in suluk, sabet, and understanding or knowledge of the Javanese Kawi language (ancient). Pandu Nur Prastiyo, at his young age, is classified as a teenager, has the expertise of a puppeteer in the traditional Javanese art of shadow puppetry, which is something rare in today's era. Usually young people his age are very familiar with rock music, pop music or other music that is more popular with modern art. Pandu Nur Prastiyo, a 4th semester student at ISI Surakarta, prefers to study the traditional Javanese art of Shadow Puppetry, an art that has been around for hundreds of years and is a favorite of the Javanese people. Keywords: biography, Pandu Nur Prasetyo,